Alterations in Brain Metabolism in Pilocarpine-Induced Epilepsy and Potential Treatment Modalities. - Zahrani, Hamsa. (2018)
Abstract: Epilepsy is one of the most common chronic neurological disorders and is manifested by abnormal hypersynchronized neuronal discharge. A cascade of molecular, neuronal and metabolic alterations are involved in the process of developing epilepsy (epileptogenesis). The exact mechanisms underlying epileptogenesis are still unclear. In order to expand our knowledge and improve our understanding of epilepsy, we have investigated two main objectives. The first objective is identifying the role of HBP1 in epilepsy. HBP1 acts as Wnt repressor, and epileptogenesis occurs when Wnt signaling is up-regulated in an HBP1 knockout mouse. Importantly, deletion of 9 genes in the HBP1 chromosomal region in human populations (7q22.3) is associated with seizure or abnormal EEG, indicating the mouse model may recapitulate human disease. Utilizing 1H and 13C NMR spectroscopy, the metabolic profile of HBP1 knock out and wild type has been quantified in hippocampus, but no significant differences were detected. The second objective in this project was testing the efficacy of the EGCG/DAC combination (a HBP1 inducer) and observing its effect on the metabolism of normal and epileptogenic brain. The EGCG/DAC is proposed to be protective against the development of epilepsy. Using NMR the metabolite concentrations were obtained. A comparison between pilocarpine induced status epilepticus and control mice revealed a series of significant metabolite alterations. In hippocampus, GABA, AMP, NAD+, were significantly decreased in the pilocarpine group compared to control mice. In contrast, concentrations of IMP, lactate, UMP and myo-inositol were significantly increased in hippocampus. Glutamate and NAA were significantly decreased in pilocarpine group. On the other hand, glutamine was significantly up regulated in pilocarpine mice in both brain regions. Also, comparisons between pilocarpine and control in the background of being treated with the drugs versus pilocarpine and control groups respectively, showed significant increase of fumarate and UDP-glucuronate in treated control and no significant change was detected in the treated pilocarpine mice. Additionally, a comparison between treated pilocarpine and treated control groups displayed no significant difference, except for the significant increase of the O-phosphoethanolamine in treated control in contrast to ethanolamine which increased significantly in treated pilocarpine group. In conclusion, besides investigating the essential signaling pathway Wnt/𝛽-catenin and HBP1, we have examined the effect of EGCG/DAC in epilepsy in order to develop a paradigm shift in treating and preventing epilepsy disorders.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: James Baleja.; Keyword: Pharmacology.